Aromatic Profile of White Sweet Semi-sparkling Wine from Malvasia di Candia Aromatica Grapes - Montevecchi, G.; Masino, F.; Vasile Simone, G.; Cerretti, E.; Antonelli, A. (South African Journal of Enology and Viticulture, 2016)
Malvasia di Candia aromatica is an aromatic white grape (Vitis vinifera L.) cultivar that grows in the Emilia-Romagna and Lombardy regions and is used for manufacturing sweet and dry white wines. A study of the gas chromatography analysis of the aromatic profile was carried out during the winemaking process for the production of a sweet semi-sparkling wine. At the end of the monitoring period, free monoterpenic and fermentative compounds characterised the aromatic profile of the wine. Linalool and nerol had a similar concentration, while the main fermentative compounds were the isoamyl alcohols, 2-phenylethanol, medium-chain fatty acids and their corresponding ethyl esters, and isoamyl acetate. All these compounds showed increasing trends during the fermentation process. The amount of linalool at the end of the monitoring period exceeded the threshold of perception, hence contributing to the floral scent of the wine. The higher alcohols (concentration up to 200 mg/L) and their esters also made a pleasant contribution to the aroma definition. Finally, the low temperature of fermentation helped to preserve the varietal aroma and enhanced the production of fermentative compounds, with a corresponding restraint of higher alcohols. This work is a first approach to a study of the sweet semi-sparkling wine (vino frizzante) obtained from Malvasia di Candia aromatica grapes. A more detailed investigation is required to understand how to improve the varietal and fermentative aromas of the wine.